Carbon dioxide selective mixed matrix composite membrane containing ZIF-7 nano-fillers - Li, Tao; Pan, Yichang; Peinemann, Klaus-Viktor; Lai, Zhiping (Journal of membrane science, 2013)
Mixed matrix materials made from selective inorganic fillers and polymers are very attractive for the manufacturing of gas separation membranes. But only few of these materials could be manufactured into high-performance asymmetric or composite membranes. We report here the first mixed matrix composite membrane made of commercially available poly (amide-b-ethylene oxide) (Pebax®1657, Arkema) mixed with the nano-sized zeolitic imidazole framework ZIF-7. This hybrid material has been successfully deposited as a thin layer (less than 1μm) on a porous polyacrylonitrile (PAN) support. An intermediate gutter layer of PTMSP was applied to serve as a flat and smooth surface for coating to avoid polymer penetration into the porous support. Key features of this work are the preparation and use of ultra-small ZIF-7 nano-particles (around 30–35nm) and the membrane processability of Pebax®1657. SEM pictures show that excellent adhesion and almost ideal morphology between the two phases has been obtained simply by mixing the as-synthesized ZIF-7 suspension into the Pebax®1657 dope, and no voids or clusters can be observed. The performance of the composite membrane is characterized by single gas permeation measurement of CO2, N2 and CH4. Both, permeability (PCO2 up to 145barrer) and gas selectivity (CO2/N2 up to 97 and CO2/CH4 up to 30) can be increased at low ZIF- loading. The CO2/CH4 selectivity can be further increased to 44 with the filler loading of 34wt%, but the permeability is reduced compared to the pure Pebax®1657 membrane. Polymer chain rigidification at high filler loading is supposed to be a reason for the reduced permeability. The composite membranes prepared in this work show better performance in terms of permeance and selectivity when compared with asymmetric mixed matrix membranes described in the recent literature. Overall, the ZIF 7/Pebax mixed matrix membranes show a high performance for CO2 separation from methane and other gas streams. They are easy to fabricate, which makes them attractive for industrial scale gas separation. ► ZIF-7 nano-particles have been synthesized and dispersed in a polymer matrix. ► High performance ZIF-7 mixed matrix membranes for gas separation were manufactured. ► Excellent compatibility between filler and polymer was observed. ► Defect-free membranes could be prepared by a simple coating technique. ► The CO2/CH4 selectivity could be more than doubled by the ZIF-7 nano-fillers.